EVALUATION OF TOTAL FACTOR PRODUCTIVITY CHANGE IN SERBIAN FARMS - Miljatović, Aleksandar (Journal on Processing and Energy in Agriculture, 2025)
The main aim of the research is to examine the productivity change across farms with different types of production. The study focuses on family farms in the Republic of Serbia that were part of the FADN (Farm Accountancy Data Network) sample over a seven-year period (2015-2021). The Malmquist index is used to calculate the total factor productivity (TFP) change during the observed period, in conjunction with previously applied Data Envelopment Analysis (DEA). The defined model is output-oriented with constant return to scale. On the output side, it considers total output value (crop, livestock and other outputs), while the input side includes multiple variables: labour input, utilised agricultural area, intermediate consumption and total assets value. The research results have shown that the total factor productivity of the observed farms increased by 8.0% over the analysed seven-year period. The increase in farm productivity ranges from 0.3% in specialist permanent crops (vineyards and fruits) to 11.8% in specialist field crops. All farming types experienced technical progress, but field crop farms have definitely benefited the most. Field crop farms consistently acquire new and modern equipment, enabling them to achieve better outcomes with the same inputs. This undoubtedly has a positive impact on farm productivity, eventually increasing the overall economic viability of farms.